THE IDENTIFICATION OF TEST ITEMS FORM OF ENGLISH NATIONAL EXAMINATIONS OF SENIOR HIGH SCHOOL LEVEL - Rony La'biran (UKI TORAJA, 2016)
The main objective of this study is to find forms of matter that exist in the EnglishNational Examination of Senior High School (SMA) before. It is expected that theresults of research will provide a deeper understanding of the forms of matter inthe national exams in English, which can help students of Senior High School(SMA) in preparation for the English National Examination that are likely still beheld. In addition, the results of this study implied benefits also expected toprovide new knowledge in analyzing test items, to know about the character of agood test items, and the establishment of good questions of the subject matter tobe tested.In order to achieve the objectives of this study researcher found outdocuments and identified English National Examination ranging from type text inany text reading material about the making of the root, finding out the kinds oftests form were used in national exams. Each item was identified and analyzed thetest one by one to achieve the objectives of this study. The populations in thisstudy were documents of English National Examination papers in ranging from2011 to 2012. The selected samples were documents of English NationalExamination academic year 2010/2011 packet 58 and 2011/2012 packet B15.The results showed that the form of the tests item that were in the EnglishNational Examination is always different every year, although there were somethat remain the same. The dominant reading texts on the English NationalExamination were recount, descriptive, report, hortatory exposition, procedure,and discussion text. The dominant type of test used was the type of multiplechoiceitems on testing reading comprehension, and testing vocabulary. Thematerial most commonly used were